(untitled) (Iranian Journal of Kidney Diseases, 2009)
During the past decades, the number of altruistic living unrelated kidney donations has substantially increased in developed countries. However, the altruistic supply of transplantable kidneys has remained much less than the demand. As a result, severe kidney shortage has been associated with increasing number of patient deaths and increasing number of commercial transplants and transplant tourism. Studies have shown that there is still a need for living kidney donation because even all potential brain-dead donors cannot supply the escalating need for kidneys. The use of living unrelated kidney donors should be morally and ethically justified and should be compatible with ethical principles. Many experts believe that increasing number of patient deaths and commercial transplants will continue to happen if kidney donation system remains merely altruistic. While some transplant professionals support a paid and regulated system to eliminate kidney shortage, others argue that it will be destructive. Iran has a 20-year experience with a compensated and regulated living unrelated kidney donation program. This transplantation model was adopted in 1988, and successfully eliminated kidney transplant waiting list by the end of 1999. Currently, more than 50% of patients with end-stage kidney disease in Iran are living with a functioning graft. This Iranian transplantation model has many ethical successes. However, because it has not been well regulated by transplant ethicists, some ethical shortcomings have remained. Unfortunately, due to lack of interest and expertise in health authorities, the number of serious ethical failures is also increasing in this transplantation model.